The Self-Perception and Usage of Medical Apps amongst Medical Students in the United States: A Cross-Sectional Survey. (5th September 2016) - Quant, Cara; Altieri, Lisa; Torres, Juan; Craft, Noah
Abstract : Background . Mobile medical software applications (apps) are used for clinical decision-making at the point of care. Objectives . To determine (1) the usage, reliability, and popularity of mobile medical apps and (2) medical students' perceptions of app usage effect on the quality of patient-provider interaction in healthcare settings. Methods . An anonymous web-based survey was distributed to medical students. Frequency of use, type of app used, and perceptions of reliability were assessed via univariate analysis. Results . Seven hundred thirty-one medical students responded, equating to a response rate of 29%. The majority (90%) of participants thought that medical apps enhance clinical knowledge, and 61% said that medical apps are as reliable as textbooks. While students thought that medical apps save time, improve the care of their patients, and improve diagnostic accuracy, 53% of participants believed that mobile device use in front of colleagues and patients makes one appear less competent. Conclusion . While medical students believe in the utility and reliability of medical apps, they were hesitant to use them out of fear of appearing less engaged. Higher levels of training correlated with a greater degree of comfort when using medical apps in front of patients.